2021
DOI: 10.1039/d0nr08381j
|View full text |Cite
|
Sign up to set email alerts
|

pH and redox triggered doxorubicin release from covalently linked carbon dots conjugates

Abstract: Tumor microenvironment responsive drug delivery systems are potential approaches to reduce the acute toxicity caused by high-dose cancer chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…24 CQDs modified with hydrazone bonds enhanced Dox release at an acidic pH ( pH 5.5). 27 In another study, a hydrophobic cysteine-based polymer was conjugated with black phosphorus carbon dots (PCQDs) for the selective delivery of drugs in tumor cells. 28 Several CQD-based DDVs for targeted drug delivery have been described previously; however, the use of polyphenolic CQDs as DDVs has not been well reported.…”
Section: Introductionmentioning
confidence: 99%
“…24 CQDs modified with hydrazone bonds enhanced Dox release at an acidic pH ( pH 5.5). 27 In another study, a hydrophobic cysteine-based polymer was conjugated with black phosphorus carbon dots (PCQDs) for the selective delivery of drugs in tumor cells. 28 Several CQD-based DDVs for targeted drug delivery have been described previously; however, the use of polyphenolic CQDs as DDVs has not been well reported.…”
Section: Introductionmentioning
confidence: 99%
“…Anabatic drug release was observed with a single trigger; for example, DTX release reached 43.7% in the presence of 50 mM DTT at pH 7.4 and 42.0% without DTT at pH 5 after 6 h. When CLip-PC@CO-LC NPs were incubated with a release medium at pH = 5 containing DTT, DTX release reached 79.0% with a fast release after 6 h. These results may be attributed to reduction-triggered disulfide bond destruction and the charge-reversal core leading to the disruption of the CLip, indicating that the biomimetic nano-delivery system remains stable in the blood circulation system and has less drug leakage. Nevertheless, the burst release of the drug can be triggered by high GSH and low pH in the TME when the NPs reach the tumor site [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] Well-documented biocompatibility, tunable photoluminescence, excellent water solubility, ease of production, and resistance to photobleaching are among the unique characteristics of CDs. [12] Previously, we reported a carbon dots-based triple-drug delivery model that consists of two chemotherapeutic drugs and targeted ligand transferrin protein. [13] We showed that the synergistic therapeutic e cacy of the triple nano-model compared to the single drug delivery models.…”
Section: Introductionmentioning
confidence: 99%